ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN PENDEKATAN METODE JOB ORDER COSTING PADA AHS SABLON BRINGIN WETAN - Afdhilah, Nur Aini; Wicaksono, Achmad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study examines the Cost estimate of Goods Sold (COGS) applying the method of Job Order Costing at AHS Sablon Bringin Wetan, an MSMEs engaged in screen printing t-shirts and other textile products. The major purpose of the investigasion is to determine a more accurate method of calculating production costs to determine competitive selling prices. This study uses direct observation and interview techniques and is qualitatively descriptive, qualitative descriptive techniques. Research study findings indicate that the method of Job Order Costing allows MSMEs to allocate costs of direct labor, raw materials, and manufacturing overhead in more detail. COGS per t-shirt is calculated at IDR 67,000, which includes costs of direct labor, raw materials, and manufacturing overhead. The conclusion of this research is that the application of method of Job Order Costing can improve the precision of production cost estimates and help MSMEs in setting more appropriate selling prices to increase business profitability.